2020
DOI: 10.3389/fneur.2020.528056
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health, Oral Microbiota, and Incidence of Stroke-Associated Pneumonia—A Prospective Observational Study

Abstract: Stroke-associated pneumonia is a major cause for poor outcomes in the post-acute phase after stroke. Several studies have suggested potential links between neglected oral health and pneumonia. Therefore, the aim of this prospective observational study was to investigate oral health and microbiota and incidence of pneumonia in patients consecutively admitted to a stroke unit with stroke-like symptoms. This study involved three investigation timepoints. The baseline investigation (within 24 h of admission) invol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…A number of oral bacterial taxa can affect not only oral health but also contribute to the initiation and/or progression of certain types of inflammation in the respiratory tract of CF patients [ 11 , 17 , 18 ]. Poor oral health may affect lung function and increase the risk of bacterial pneumonia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of oral bacterial taxa can affect not only oral health but also contribute to the initiation and/or progression of certain types of inflammation in the respiratory tract of CF patients [ 11 , 17 , 18 ]. Poor oral health may affect lung function and increase the risk of bacterial pneumonia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend was observed by Cieplik et al, in a prospective study assessing the health and bacterial flora of the oral cavity of patients admitted to the stroke department. The researchers found that the incidence of pneumonia in patients with confirmed stroke was more frequent in patients with larger dental cavities and poorer oral hygiene [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neurological status of all patients included in the study was confirmed by early brain imaging using CT or MRI in the stroke unit. Moreover, few clinically useful tests, i.e., BI, BBS, and FIM, widely used in international classification to measure disability and functioning, were applied [ 26 , 32 , 33 , 34 , 62 , 63 ]. Therefore, the disability that affects daily living activities and the potential functional improvement of patients undergoing a rehabilitation program could be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be emphasized that knowledge concerning proper oral care in stroke patients that stay, e.g., at the rehabilitation centers and nursing home settings [ 25 ], is lacking. Some future research should focus on potential associations between diseases of the oral cavity and neglected oral hygiene [ 26 ]. Thus, more clinical studies are needed in the field to support medical professionals.…”
Section: Introductionmentioning
confidence: 99%